2020
DOI: 10.1210/clinem/dgaa777
|View full text |Cite
|
Sign up to set email alerts
|

Association of Thyroid Hormone Therapy with Mortality in Subclinical Hypothyroidism: A Systematic Review and Meta-Analysis

Abstract: Context Benefits of thyroid hormone therapy on mortality in adults with subclinical hypothyroidism remain undetermined. Objective To summarize the impact of thyroid hormone therapy on mortality in adults with subclinical hypothyroidism. Data Sources PubMed, Embase, Scopus, Web of Science, and Clinicaltrials.gov from inception until April 25, 2020. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 37 publications
0
16
0
3
Order By: Relevance
“…Previous studies have suggested that the association between hypothyroidism and mortality is less evident in individuals aged > 65 years (20,32,34,44). Recently, Peng et al found that the use of thyroid hormone replacement was not associated with all-cause mortality in patients aged > 65 years with subclinical hypothyroidism (38). The Leiden 85+ study, which enrolled individuals aged 85 years and older, indicated a decreased risk of cardiovascular and all-cause mortality with higher TSH levels (18), but these findings have not been replicated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have suggested that the association between hypothyroidism and mortality is less evident in individuals aged > 65 years (20,32,34,44). Recently, Peng et al found that the use of thyroid hormone replacement was not associated with all-cause mortality in patients aged > 65 years with subclinical hypothyroidism (38). The Leiden 85+ study, which enrolled individuals aged 85 years and older, indicated a decreased risk of cardiovascular and all-cause mortality with higher TSH levels (18), but these findings have not been replicated.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of mortality in hypothyroidism may differ by age and sex ( 18 , 20 , 24 , 28 , 32 , 34 , 38 ). Previous studies have suggested that the association between hypothyroidism and mortality is less evident in individuals aged > 65 years ( 20 , 32 , 34 , 44 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Five observational studies and two randomized controlled trials (with a total of 21,055 patients) were included. The results showed that LT4 therapy was associated with a significant reduction in all-cause (RR = 0.50, CI 0.29–0.85, p = 0.011) and cardiovascular (RR = 0.54, 95% CI 0.37–0.80, p = 0.002) mortality in patients younger than 65 years, but not in older patients [ 34 ].…”
Section: Thyroid Alterations and Cvdmentioning
confidence: 99%
“…Eine aktuelle Metaanalyse mit 21 055 Erwachsenen belegte in einer Subgruppenanalyse bei Erwachsenen < 65-70 Jahre, dass eine Schilddrüsenhormonsubstitution bei subklinischer Hypothyreose signifikant mit einer geringeren kardiovaskulären Mortalität und Gesamtmortalität assoziiert war [15].…”
Section: Umweltfaktorenunclassified